PERILAKU PENGGUNAAN PLATFORM KESEHATAN DIGITAL SEBAGAI SOLUSI LAYANAN KESEHATAN PADA PANDEMI COVID-19 (Value : Jurnal Manajemen dan Akuntansi, 2022)
The Covid-19 pandemic that has occurred in Indonesia since March 2020 has changed people's behavior, including in the health sector. People use digital health platforms, because hospitals are considered to be places with a high risk of transmitting the Covid-19 virus. People are not willing to visit the hospital even though they are sick and need a doctor. The purpose of this study was to determine the effect of integrity, benevolence, trust, and continuance intention on digital health platform users. The study used quantitative methods through the distribution of online questionnaires. Data processing using SmartPLS 3.0. The results show that integrity, benevolence and trust have an effect on continuance intention on digital health platforms.Keywords: telemedicine, integrity, benelovence, trust, continuance intention